ARJASA VILLAGE AS A SOCIAL EDUCATION LABORATORY TO DEVELOP SPATIAL LITERACY - Depict Pristine Adi; Enok Maryani (JURNAL ILMIAH DIDAKTIKA: Media Ilmiah Pendidikan dan Pengajaran, 2024)
This research aims to determine the potential of Arjasa Village as a social studies laboratory in developing students' spatial literacy and to identify the village's spatial potential as an aspect of spatial literacy. Spatial literacy is an individual's ability to understand space comprehensively, including interactions between spaces, scale, analysis, representation, and application. This research uses descriptive qualitative research, with the selection of informants using purposive techniques to explore participants' experiences and perceptions in depth, thereby enabling a richer understanding of how spatial literacy is reflected in the lives of the people of Arjasa Village. This research shows that Arjasa Village has fulfilled six characteristics of spatial literacy: comprehensiveness, spatial interaction, scale, analysis, representation, and application. Arjasa Village can be used as a location to develop spatial literacy. Apart from that, Arjasa Village also has many sites and phenomena that can be used as learning resources, especially in developing a social studies laboratory